Edukasi Menghadapi Era Digital Keuangan & Resiko Teknologi Finansial Melalui “Sekolah Media Literasi” (SMILE) - Ade Putranto Prasetyo Wijiharto Tunggali; Komarudin Komarudin; Widyo Nugroho (Madani : Indonesian Journal of Civil Society, 2026)
The rapid growth of digital technology has transformed traditional gambling activities—such as poker, casinos, mahjong, sports betting, cockfighting, dice games, lottery, and numbers gambling—into increasingly popular online practices. Although often perceived as entertainment, online gambling has significant negative impacts on social life. Addressing this issue requires collaboration among various stakeholders, including educational institutions that play a vital role in promoting media and financial literacy. The Faculty of Communication Sciences at Gunadarma University has taken part through the SMILE (School of Media Literacy) program, which focuses on financial literacy education. This program is implemented through counseling, mentoring, and training using presentations, interactive media, and focus group discussions. The results indicate an improvement in community understanding of healthy financial management. Nevertheless,  such educational efforts should not be one-time initiatives but rather continuous activities in order to build a society that is financially literate, independent, and resilient against the negative impacts of online gambling.